Mimicking the cauda epididymal plasma-like osmolality in extender improves liquid preservation of ram semen at 3–5°C. (2nd November 2019) - Paul, Rajani Kumar; Balaganur, Krishnappa; Kumar, Davendra; Singh, Raghvendar
ABSTRACT: Cauda epididymis in mammals is known to store mature sperm largely in quiescent state for several weeks without significantly affecting fertility. Hence, the aim of this study was to evaluate the effects of mimicking cauda epididymal plasma (CEP)-like conditions in extender on liquid preservation of ram semen at 3–5°C. Four experiments were conducted in this study: (1) evaluation of physicochemical properties of ram CEP, (2) effect of hyperosmotic solution on sperm motility and functional membrane integrity (FMI), and the effects of (3) CEP-like hyperosmolality (390 vs. 360 mOsmol/kg) and (4) pH in extender (pH 6.5 vs. 6.8) on liquid preservation of ram semen. Sperm treatment with hyperosmotic solution (450 mOsmol/kg) resulted in a decline (P < 0.05) in mass motility (3.5 ± 0.2 vs. 4.3 ± 0.2) and FMI (30.4 ± 3.2 vs. 52.1 ± 2.1%) compared to that with isoosmotic solution (360 mOsmol/kg). Overall, sperm viability, acrosomal integrity, and progressive motility were similar (P > 0.05) while straight-line velocity (77.8 ± 3.1 vs. 71.3 ± 2.7µm/s), linearity (47.4 ± 0.4 vs. 39.5 ± 0.9%), straightness (79.7 ± 0.5 vs. 74.0 ± 0.5%) and beat cross frequency (28.6 ± 0.8 vs. 26.0 ± 0.5 Hz) were higher (P < 0.05) and FMI (65.7 ± 1.5 vs. 75.4 ± 1.1%) was lower (P < 0.05) following liquid-preservation in hyperosmotic extender compared to that in isoosmotic extender. Both total motility (83.3 ± 1.8 vs. 75.4 ± 1.5%) and progressive motility (51.7 ± 2.3 vs. 39.5 ± 1.9%) were higher (P < 0.05) at 48 h of storage in hyperosmotic extender compared to the control. Overall, the seminal attributes were similar (P > 0.05) between the two pH's of the extender. In conclusion, semen extender having CEP-like osmolality but not the pH was superior to extenders having conventional osmolality and pH for liquid preservation of ram semen. Abbreviations : AI: artificial insemination; ALH: amplitude of lateral head displacement; BCF: beat cross frequency; CASA: computer-assisted semen analyzer; CEP: cauda epididymal plasma; ELON: elongation; EYTF: egg yolk-Tris-citrate-fructose; FMI: functional membrane integrity; GLM: general linear model; GPC: glycerophosphatidylcholine; HOS: hypoosmotic swelling; LIN: linearity; pHe: external pH; PROG: progressive motility; S.E.M.: standard error of the mean; SLTF: soya lecithin-Tris-fructose extender; SP: seminal plasma; STR: straightness; VAP: average path velocity; VCL: curvilinear velocity; VSL: straight-line velocity; TM: total motility